"If I Am Ready": Exploring the relationships between masculinities, pregnancy, and abortion among men in James Town, Ghana. (December 2022) - Strong, Joe; Lamptey, Nii Lartey Samuel; Quartey, Nii Kwartelai; Owoo, Nii Kwartei Richard
Abstract: The ability to exercise full sexual and reproductive health and rights is shaped by the contextual environment, meaning that women and pregnant people must navigate patriarchal norms when seeking care. Despite growing evidence that men are able to influence pregnancy outcomes, there remains a paucity of research on how and why men are able to involve themselves in pregnancy and abortion decision-making. This study interrogates the mechanisms that drive men's involvement in pregnancies and abortions in James Town, Ghana. Data from a survey (n = 296) and in-depth interviews (n = 37) were collected between July 2020 and January 2021. The mixed-method analysis critically examined the relationship between men's support for a pregnancy or abortion and their constructions of masculinities. Findings framed sex and reproduction as both a facilitator and a threat to men's masculinity. Reproduction was an essential component of being a man. Men discussed the need to fulfil masculine ideals of being independent, provide financially, and be in an acceptable relationship in order to be 'ready' for fatherhood. However, men similarly operationalised the notion of 'readiness' as the driving force behind their involvement in abortion decision-making. As being a father without being ready could lead to social ostracism and derision, men discussed forcing their abortion desires onto their sexual partners and other pregnant people. Achieving masculine ideals, therefore, was a critical motivation for controlling women and pregnant people's bodies. Understanding the role of masculinities is critical in acknowledging the contextual and environmental factors that women and pregnant people navigate, which contribute to continued reproductive injustices. Highlights: Masculine norms are shaped by ideals of sex, reproduction, fatherhood, and providing. Men develop norms around being 'ready' for fatherhood that determine their support for a pregnancy. Men used abortions to facilitate ideals of manhood, rooted in 'readiness' for a live birth. Abortion attitudes among men were not static and depending on the relationship to a person. Masculinities contribute towards the conditions pregnant people have to navigate.